Analisis Dekonstruksi Jacques Derrida Dalam Pergeseran Makna Pakaian - Mubarok, Achmad Sofiyul; Pratama, Yuda; Liansi, Tomi (Indonesian Journal of Islamic Theology and Philosophy, 2024)
Abstract;This article will explore the essence of clothing in the era of disruption that has a function as a body protector and becomes the identity of a human being. However, the clothes referred to in this article are not physical clothes, but inner/pious clothes. The quality of clothing that is dhohir reflects a person's identity. So that the capitalization of clothing in modern times is prone to occur. Unlike the inner clothes, the quality of human piety is determined by their own hearts. So that the behavior that is done has profane values and a piety cannot be capitalized. Because, the best clothes for Muslims are the clothes of piety. This research uses a qualitative method and this research aims to reveal the meaning and interpretation with Jacques Derrida's Deconstruction theory. Deconstruction aims to dismantle a single meaning and produce infinite meanings. The results of this study reveal that the interpretation in the classical era was limited to understanding takwa clothing as faith in God and the recommendation to cover the veil. Meanwhile, in modern interpretations, this verse is understood as a form of servitude to Allah Swt and highlights the active role of humans in wearing clothes.Keywords:Al-A’raf:26; Clothing; Dekonstruksi. Abstrak;Artikel ini akan mengeksplorasi esensi pakaian dalam era disrupsi yang memiliki fungsi sebagai pelindung badan dan menjadi identitas seseorang manusia. Namun pakaian yang dimaksud pada artikel ini bukanlah pakaian secara dhohir, tetapi pakaian batin/takwa. Kualitas pakaian yang sifatnya dhohir mencermikan sebuah identitas seseorang. Sehingga kapitalisasi pakaian di zaman modern ini rentan terjadi. Berbeda dengan pakaian batin/takwa, kualitas takwa manusia ditentukan oleh hati mereka sendiri. Sehingga perilaku yang diperbuat memiliki nilai-nilai profan dan sebuah ketakwaan tidak akan bisa dikapitalisasi. Karena, sebaik-baiknya pakaian bagi orang muslim adalah pakaian takwa. Penelitian ini menggunakan metode kualitatif dan penelitian ini bertujuan mengungkap makna dan penafsiran dengan teori Dekonstruksi Jacques Derrida. Dekonstruksi bertujuan untuk membongkar makna tunggal dan menghasilkan makna yang tak terbatas. Hasil penelitian ini mengungkapkan bahwa penafsiran pada era klasik terbatas pada pemahaman pakaian takwa sebagai iman kepada Tuhan dan anjuran untuk menutup aurat. Sementara itu, dalam tafsir modern, ayat ini dipahami sebagai bentuk penghambaan kepada Allah Swt dan menyoroti peran aktif manusia dalam pemakaian pakaian.Kata Kunci:   Al-A’raf: 26; Dekontruksi; Pakaian.